1983
DOI: 10.1172/jci110868
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase Pathway in Islet Endocrine Cells. OXIDATIVE METABOLISM OF ARACHIDONIC ACID PROMOTES INSULIN RELEASE

Abstract: A B S T R A C T Metabolism of arachidonic acid (AA) via the cyclooxygenase pathway reduces glucose-stimulated insulin release. However, metabolism of AA by the lipoxygenase pathway and the consequent effects on insulin secretion have not been simultaneously assessed in the endocrine islet. Both dispersed endocrine cell-enriched pancreatic cells of the neonatal rat, as well as intact islets of the adult rat, metabolized [3H]AA not only to cyclooxygenase products (prostaglandins E2, F2a, and prostacyclin) but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 62 publications
3
45
0
Order By: Relevance
“…We now provide evidence that the 5-LO/LT pathway is another mechanism by which such processes are regulated. Importantly, our observations are in agreement with a series of earlier studies carried out by Metz et al demonstrating that lipoxygenase inhibitors decrease glucose-stimulated insulin secretion in a dose-dependent manner [27,28] and that arachidonic acid metabolites play a role as 'third messengers' for hormone release [29,30]. More recently, Prasad and colleagues have shown that 12/15-LO, a related enzyme that also metabolises arachidonic acid, influences beta cell function and insulin secretion as well [31].…”
Section: Discussionsupporting
confidence: 92%
“…We now provide evidence that the 5-LO/LT pathway is another mechanism by which such processes are regulated. Importantly, our observations are in agreement with a series of earlier studies carried out by Metz et al demonstrating that lipoxygenase inhibitors decrease glucose-stimulated insulin secretion in a dose-dependent manner [27,28] and that arachidonic acid metabolites play a role as 'third messengers' for hormone release [29,30]. More recently, Prasad and colleagues have shown that 12/15-LO, a related enzyme that also metabolises arachidonic acid, influences beta cell function and insulin secretion as well [31].…”
Section: Discussionsupporting
confidence: 92%
“…12LO was initially thought to be physiologically important in regulating glucose-stimulated insulin release in pancreatic islets of Langerhans [10][11][12][13]. More recent evidence has suggested that 12LO plays a role in inflammation and metabolic-stress-induced islet functional abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 12LO may have profound effects on cell metabolism and survival [24,25]. In addition, 12LO products are recognised as intracellular signalling molecules capable of activating specific protein kinases [26,27], translocating to specified cellular compartments [10], or modifying gene expression. Recent data also show that macrophages from the 12LO-null mouse lack IL-12 expression and production [28].…”
Section: Introductionmentioning
confidence: 99%
“…Isolated pancreatic islets from rats and humans convert endogenous arachidonic acid to oxygenated metabolites, and islet eicosanoid synthesis is stimulated by insulin secretagogues (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The most abundant islet eicosanoids are the cyclooxygenase product PGE 2 1 and the 12-lipoxygenase product 12-hydroxy- (5,8,10,14)-eicosatetraenoic acid .…”
mentioning
confidence: 99%
“…Fuel insulin secretagogues stimulate islet 12-HETE production; exogenous 12-HPETE, the precursor of 12-HETE, stimulates insulin secretion (1); and pharmacologic inhibitors of 12-lipoxygenase suppress both 12-HETE production and insulin secretion with identical concentration dependences (1)(2)(3)(4)(5)(6)(7)(8). Islet 12-HETE consists exclusively of the S-enantiomer, indicating enzymatic synthesis (9), and immunochemical analyses indicate that islet 12-lipoxygenase is selectively expressed in ␤-cells but not in ␣-cells or in pancreatic exocrine cells (18).…”
mentioning
confidence: 99%